Pemanfaatan Dana Desa Untuk Meningkatkan Kesejahteraan Masyarakat Melalui Promosi Produk UMKM Menggunakan Collaborative Filtering Berbasis Android - Siahaan, Agus Maringan; Robet; Jonathan Kevin Fernando; Donna Natalia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Utilizing village funds through Badan Usaha Milik Desa (BUMDes) is a strategic effort to improve the welfare of rural communities. However, its implementation often faces challenges such as suboptimal management of local economic potential and limited promotion of Micro, Small, and Medium Enterprises (MSMEs) products. This study aims to develop an Android-based application utilizing the Collaborative Filtering method as an innovative solution to support the promotion of village MSME products, enhance the effective use of village funds, and drive economic growth in rural areas. The application is designed to provide MSME product recommendations based on user preferences. Integrating the Collaborative Filtering method, the application analyzes user interaction data to offer relevant product suggestions. Its key features include product search, personalized recommendations, and a user-friendly interface that is easy for rural communities to operate. The black-box method testing results show that this application works according to the designed specifications with a system interface functional success rate of 100% of 31 functional interfaces. increased the promotion and sales of local MSME products.